2014
DOI: 10.1080/00958972.2014.931947
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II), nickel(II), and ruthenium(III) complexes of an oxopyrrolidine-based heterocyclic ligand as anticancer agents

Abstract: An oxopyrrolidine-based ligand [3-(4-chlorobenzylidine)-5-(5-amino-1,3,4-thiadiazol-2-yl)pyrrolidin-2-one] was synthesized by coupling pyroglutamic acid with p-chlorobenzaldehyde followed by cyclization with thiosemicarbazide in presence of oxyphosphoryl chloride. Copper, nickel, and ruthenium complexes of the ligand were also synthesized. The electrolytic nature, with octahedral geometries for nickel and ruthenium complexes, was observed, while tetragonally distorted octahedral geometry for copper complex was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…The IC 50 value of synthesized complexes compares well with those reported for cytotoxic copper(II) complexes giving IC 50 values in similar concentration range [11][12][13][14][15]. This study suggests that 1 and 2 have potential as anticancer agents.…”
Section: Cell Proliferation Assay (Mtt)supporting
confidence: 85%
See 1 more Smart Citation
“…The IC 50 value of synthesized complexes compares well with those reported for cytotoxic copper(II) complexes giving IC 50 values in similar concentration range [11][12][13][14][15]. This study suggests that 1 and 2 have potential as anticancer agents.…”
Section: Cell Proliferation Assay (Mtt)supporting
confidence: 85%
“…Macrocyclic dicopper(II) complexes have shown cytotoxicity in human cervical HeLa cancer cells lines [14]. Recently, Wani et al have reported the moderate cytotoxic activity of a Cu(II) complex based on oxopyrrolidine-based heterocyclic ligand [15]. In the present paper, both Cu(II) complexes were assessed for their possible antimicrobial and cytotoxic properties.…”
Section: Introductionmentioning
confidence: 95%
“…DNA is among the most significant pharmaceutical targets of anticancer medications. Thus, studying the interactions of target compounds with DNA is important to get an indication about their anticancer impacts and imaginable mechanisms of action. In general, a compound and DNA formed covalent and noncovalent bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Imine based Schiff bases like N-hydroxy-N‫-׳‬ aminoguanidine L 20 block ribo-nucleotide reductase in tumor cells, hence they are used in the treatment of leukemia [17]. Similarly Schiff bases based on cumarin and pyrazole aldehyde L 24 showed mild anti-cancerous capabilities [19]. Some mono and bis-Schiff bases are effective against five cancer cell lines [20].…”
Section: Anticancer Activitiesmentioning
confidence: 99%